Korelasi Kadar Total Logam Pb Terhadap Kadar Protein Pada Udang Putih (Penaeus marguiensis) Yang Diambil Dipesisir Pulau Bunyu Kalimantan Utara - Rudi Kartika (JURNAL KIMIA MULAWARMAN, 2017)
Research on "Correlation levels of Pb to the total protein content in the white shrimp (Penaeus merguiensis) taken around the coast of North Borneo Bunyu Island". This study aims to determine the total concentration of Pb and protein levels in white shrimp by size and sampling different regions. then the total levels of Pb and protein correlated with Least Square method. Analysis of Pb total metal content by using AAS (Atomic Absorption Spectrophotometer) and analysis of protein content using the Kjeldahl method. In this study, the levels of Pb total in area 1 with an average of 0,738 mg/L, the levels of Pb total in area 2 with an average of 0.926 mg/L, the levels of Pb total area 3 with an average of 0,841 mg/L. The protein content of white shrimp in area 1 with an average of 27,8644%, protein content in area 2 gained an average of 29,0333% and 3 area gained an average protein content of 27,8635%. Correlation levels of Pb total the protein content of the white shrimp (Penaeus merguiensis) r = 0.877